Clarithromycin reduces recurrent cardiovascular events in subjects without periodontitis - DOĞAN, BAŞAK (ELSEVIER IRELAND LTD, 2006)
Inflammation leading to acute coronary syndrome may be triggered by bacteria causing periodontal infection. We investigated if recurrence of cardiovascular events in unstable coronary patients are associated with periodontitis or microbiological/serological markers of it. Periodontitis-related parameters of 141 patients with acute non-Q-wave infarction or unstable angina pectoris, who participated in a double-blind, placebo-controlled study with clarithromycin for 3 months, were adjusted to the occurrence of a recurrent cardiovascular event during a follow-up period (average 519 days). In the age group under 65 years the patients with periodontitis had a univariate odds ratios (OR) 95% confidence intervals (95% CI) of 5.0 (1.02-24.55) for a recurrent cardiovascular event in comparison with patients without periodontitis. Dental status correlated positively with serum lipopolysaccharide concentrations and combined IgG antibody response to Actinobacillus actinoinycetemcomitans and Porphyromonas gingivalis. The end point frequency did not differ between clarithromycin and placebo groups in bacterium-positive, seropositive, or periodontitis patients. Fewer end points in clarithromycin group were seen in bacterium-negative, seronegative, edentulous, and non-periodontitis patients. Periodontitis and edentulousness are associated with recurrent cardiovascular events, especially in younger patients. Long-term clarithromycin therapy seems to be beneficial in prevention of recurrent cardiovascular events in non-periodontitis but not in periodontitis patients. (c) 2005 Elsevier Ireland Ltd. All rights reserved.
Keywords: inflammation; coronary disease; acute coronary syndrome; periodontitis; lipopolysaccharide; CORONARY-HEART-DISEASE; ACUTE MYOCARDIAL-INFARCTION; ORAL INFECTIONS; ASSOCIATION; PATHOGENS; EPIDEMIOLOGY; ERYTHROMYCIN; ANTIBIOTICS; PREVENTION; ANTIBODIES